Rethink the notion of “migratory crisis”: For an ethical and humanitarian journalistic coverage of the dynamics of human mobility - Dutra Brignol, Liliane; Curi, Guilherme (Estudios sobre el Mensaje Periodístico, 2021)
In this article, at first, we seek to problematize the notion of “migratory crisis” and discuss the role of the media, especially journalism, in the construction of meanings about the contemporary dynamics of human mobility. From this central criticism presented, we describe the experience of an extension course for communicators on transnational migrations. Thus, we raise perspectives that allow us to understand the idea of ​​crisis associated with migrations as a discursive strategy. As presented, it reinforces the construction of fear of the other when positioning the human displacement in the insurance sphere and that crystallizes the understanding of migration as an isolated problem, which can be solve only within the limits of the national state. Ultimately, we aim to contribute to the proposition of new grammars and approaches on transnational migrations in the media field, which consider the need for ethical and humanitarian confrontation that the theme requires.